New psychological contracts, old breaches? - Costa, S. (Redefining the psychological contract in the digital era: Issues for research and practice, 2021)
The psychological contract—individual’s beliefs about the terms and conditions of a reciprocal agreement with the organization—has been changing since the 1990s. This change is a result of labor market pressures, trends, and technology. Today, work and workplaces are more dynamic and digitalized than ever and expectations from employers and employees are shaped by these factors. However, the expectation about the fulfillment of employer obligations and promises (regardless of what these obligations may be) seems to be the same. This chapter highlights the changes from the old to the new psychological contract, and from the new psychological contract to emergent forms of psychological contracts. Moreover, it also discusses whether these changes may (or may not) impact employees’ perceptions of breach and violation, by discussing content and measurement issues and suggesting future research directions.